The conditional impact of market consolidation and market power on banking stability – Evidence from Europe - Herwald, Sarah; Voigt, Simone; Uhde, André (Journal of Risk Finance)
Purpose Academic research has intensively analyzed the relationship between market concentration or market power and banking stability but provides ambiguous results, which are summarized under the concentration-stability/fragility view. We provide empirical evidence that the mixed results are due to the difficulty of identifying reliable variables to measure concentration and market power. Design/methodology/approach Using data from 3,943 banks operating in the European Union (EU)-15 between 2013 and 2020, we employ linear regression models on panel data. Banking market concentration is measured by the Herfindahl–Hirschman Index (HHI), and market power is estimated by the product-specific Lerner Indices for the loan and deposit market, respectively. Findings Our analysis reveals a significantly stability-decreasing impact of market concentration (HHI) and a significantly stability-increasing effect of market power (Lerner Indices). In addition, we provide evidence for a weak (or even absent) empirical relationship between the (non)structural measures, challenging the validity of the structure-conduct-performance (SCP) paradigm. Our baseline findings remain robust, especially when controlling for a likely reverse causality. Originality/value Our results suggest that the HHI may reflect other factors beyond market power that influence banking stability. Thus, banking supervisors and competition authorities should investigate market concentration and market power simultaneously while considering their joint impact on banking stability.
Keywords: market concentration; market power; banking stability; European banking

The conditional impact of market consolidation and market power on banking stability – Evidence from Europe - Herwald, Sarah; Voigt, Simone; Uhde, André

Risk allocation through securitization – Evidence from non-performing loans - Wengerek, Sascha Tobias; Hippert, Benjamin; Uhde, André (The Quarterly Review of Economics and Finance)
Employing a unique and hand-collected sample of 648 true sale loan securitization transactions issued by 57 stock-listed banks across the EU-12 plus Switzerland over the period from 1997 to 2010, this paper empirically analyzes the relationship between true sale loan securitization and the issuing banks’ non-performing loans to total assets ratios. Overall, we provide evidence for a negative impact of securitization on NPL exposures suggesting that banks predominantly used securitization as an instrument of credit risk transfer and diversification. In addition, the analysis at hand reveals a time-sensitive relationship between securitization and NPL exposures. While we observe an even stronger NPL-reducing effect through securitization during the non-crisis periods, the effect reverses during and after the global financial crisis suggesting that banks were forced to provide credit enhancement and employ securitization as a funding management tool. Along with the results from a variety of sensitivity analyses our study provides important implications for the recent debate on reducing NPL exposures of European banks by revitalizing the European securitization market.
Keywords: European Banking; Non-performing Loans; Securitization

Semiparametric GARCH models with long memory applied to Value at Risk and Expected Shortfall - Letmathe, Sebastian; Feng, Yuanhua; Uhde, André (Journal of Risk)
In this paper new semiparametric generalized autoregressive conditional heteroscedasticity (GARCH) models with long memory are introduced. A multiplicative decomposition of the volatility into a conditional component and an unconditional component is assumed. The estimation of the latter is carried out by means of a data-driven local polynomial smoother. According to the revised recommendations by the Basel Committee on Banking Supervision to measure market risk in the banks’ trading books, these new semiparametric GARCH models are applied to obtain rolling one-step ahead forecasts for the value-at-risk and expected shortfall (ES) for market risk assets. Standard regulatory traffic-light tests and a newly introduced traffic-light test for the ES are carried out for all models. In addition, model performance is assessed via a recently introduced model selection criterion. The practical relevance of our proposal is demonstrated by a comparative study. Our results indicate that semiparametric long-memory GARCH models are a meaningful substitute for their conventional, parametric counterparts.
Keywords: long memory; generalized autoregressive conditional heteroscedasticity (GARCH) models; value-at-risk (VaR); expected shortfall (ES); traffic-light test; backtesting

Tax avoidance through securitization - Uhde, André (The Quarterly Review of Economics and Finance)
Employing a unique hand-collected sample of 956 credit risk securitization transactions issued by 64 stock-listed European banks across the EU-13 plus Switzerland over the period from 1997 to 2010, this paper empirically analyzes the impact of securitization on the issuing banks’ effective tax rates. Our analysis reveals that banks may reduce their tax expense through securitization via a direct and indirect channel suggesting that tax avoidance may be a further motive for banks to engage in the securitization business. These baseline findings remain robust under various robustness checks, especially when implementing structural equation models and controlling for a reverse causality between the banks’ tax burden and their incentive to securitize. Finally, various sensitivity analyses provide further important results and implications for tax policies, banking regulation and the ongoing process of revitalizing the European securitization market.
Keywords: Securitization; Credit risk transfer; Effective tax rates; European banking

CDS Investors’ Risk Perceptions of M&A Announcements - Hippert, Benjamin; Uhde, André
Merging a sample of 492 merger and acquisition (M&A) announcements from 284 acquiring firms across Europe and North America with data from 5-year single-name credit default swaps (CDSs) written on stock-listed acquiring firms between 2005 and 2018, the paper at hand empirically analyzes the CDS investors’ risk perceptions of M&A announcements using event study methodologies. As a baseline result, we provide evidence for significantly positive cumulative average abnormal CDS spread changes for both, European and North American acquirers suggesting that CDS investors perceive an increase in the acquiring firms’ credit risk exposures due to M&A announcements. Our baseline finding holds under several robustness checks, especially when controlling for the robustness of the empirical design. Moreover, results from a large variety of sensitivity analyses reveal a number of deal and firm characteristics that may explain why CDS investors from our sample expect an increase in the acquirers’ credit risk exposures due to forthcoming M&A transactions.
Keywords: credit default swaps; risk perception of CDS investors; mergers and acquisitions; event study

Determinants of CDS Trading on Major Banks - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias
This paper empirically investigates determinants of the outstanding net notional amount of credit default swaps (CDSs) contracts written on banks. We extend and complement the previous literature dealing with CDS trading by analyzing a comprehensive set of CDS tradingspecific, bank-fundamental, macroeconomic and bank-institutional determinants. We find that risk hedging clearly dominates an investor’s speculation and arbitrage motive, while the latter, however, exhibits the strongest impact on the outstanding net notional amount of bank CDSs. Furthermore, being classified as a G-SIB, being a constituent of the main CDS index and the equity trading volume may significantly explain changes in the outstanding CDS net notional on banks. The analysis at hand provides important implications for both academics and practitioners, since understanding the trading motives of bank CDS investors provides a deeper insight into the opaque CDS market.
Keywords: banking; outstanding CDS net notional; determinants of bank CDS trading

The relationship between announcements of complete mergers and acquisitions and acquirers' abnormal CDS spread changes - Hippert, Benjamin
Employing a sample of 492 merger and acquisition (M&A) announcements from 284 acquirers across North America and Europe between 2005 and 2018, this study analyzes the impact of M&A announcements on an acquirers abnormal CDS spread changes. We find that spreads from CDS which are written on acquirers increase by 310 bps during a symmetric five-day event window suggesting that investors expect an increase in the acquirers credit risk exposure due to M&As. Next to this baseline finding, we conduct a large variety of sensitivity analyses to gain more insight into the driving factors of the rising risk perception of CDS investors due to M&A announcements.
Keywords: credit default swaps; risk perception of CDS investors; mergers and acquisitions; event study

Portfolio Benefits of Adding Corporate Credit Default Swap Indices: Evidence from North America and Europe - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias (Review of Derivatives Research)
Employing main and sector-specific investment-grade CDS indices from the North American and European CDS market and performing mean-variance out-of-sample analyses for conservative and aggressive investors over the period from 2006 to 2014, this paper analyzes portfolio benefits of adding corporate CDS indices to a traditional financial portfolio consisting of stock and sovereign bond indices. As a baseline result, we initially find an increase in portfolio (downside) risk-diversification when adding CDS indices, which is observed irrespective of both CDS markets, investor-types and different sub-periods, including the global financial crisis and European sovereign debt crisis. In addition, the analysis reveals higher portfolio excess returns and performance in CDS index portfolios, however, these effects clearly differ between markets, investor-types and sub-periods. Overall, portfolio benefits of adding CDS indices mainly result from the fact that institutional investors replace sovereign bond indices rather than stock indices by CDS indices due to better risk-return characteristics. Our baseline findings remain robust under a variety of robustness checks. Results from sensitivity analyses provide further important implications for institutional investors with a strategic focus on a long-term conservative portfolio management.
Keywords: Corporate credit default swap indices; Mean-variance asset allocation; Out-of-sample portfolio optimization; Portfolio risk-diversification; Portfolio performance evaluation

Share price reactions to tariff imposition announcements in the Trump era – An event study of the trade conflict - Wengerek, Sascha Tobias; Uhde, André
Employing a unique sample of 2,849 tariff imposition announcements by and against the United States (U.S.) over the period from 2018 to 2019, this study analyzes the impact of recent tariff announcements on share prices from 859 U.S. companies. We provide evidence for negative (cumulative) average abnormal stock returns due to tariff announcements during a symmetric three-day event window. We suggest that stock market investors expect adverse impacts of tariff impositions, e.g. a decrease in the companies' future cash flows and a threat of retaliation. The negative wealth effects are observed irrespective of whether the Trump administration announces safeguard tariffs to protect domestic firms or a retaliation is declared by foreign countries. Moreover, building several subsamples, we find that the adverse impact is mostly driven by announcements involving China and is associated with a variety of sector, tariff, trade and firm characteristics.
Keywords: event study; international relations; protectionism; strategic trade policy; tariffs; trade conflict